2011
DOI: 10.1103/physrevlett.107.253602
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Realization of Optimal Noise Estimation for a General Pauli Channel

Abstract: We present the experimental realization of the optimal estimation protocol for a Pauli noisy channel. The method is based on the generation of 2-qubit Bell states and the introduction of quantum noise in a controlled way on one of the state subsystems. The efficiency of the optimal estimation, achieved by a Bell measurement, is shown to outperform quantum process tomography.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 22 publications
(32 reference statements)
0
48
0
Order By: Relevance
“…It is therefore much cheaper than full process tomography and it can be easily accessed in the lab without posing any particular restriction on the nature of the physical system under consideration. In particular, for quantum optical systems it is easily implementable with present-day technologies [21]. We tested the method for significant qubit channels and it turned out to give extremely good results for various forms of noise.…”
mentioning
confidence: 99%
“…It is therefore much cheaper than full process tomography and it can be easily accessed in the lab without posing any particular restriction on the nature of the physical system under consideration. In particular, for quantum optical systems it is easily implementable with present-day technologies [21]. We tested the method for significant qubit channels and it turned out to give extremely good results for various forms of noise.…”
mentioning
confidence: 99%
“…We notice that two-qubit logic gate and single-qubit gate have been experimentally observed in several physical systems including trapped ions [49], optical system [50], a semiconductor quantum dot [51], neutral atoms [52], and diamond nitrogen-vacancy centers [53]. On the other hand, the experimental realization of the noisy environments such as dephasing noise, bitflip noise, and anisotropic Pauli noises has been reported with linear optical elements [41,54,55]. What is more, Liu et al [56] have recently demonstrated an all-optical experiment which allows one to drive the open quantum system from the Markovian to the non-Markovian regime and to control the information flow between the system and the environment.…”
Section: Discussionmentioning
confidence: 97%
“…The two crystals are tuned in such a way that they perform a rapid succession of Pauli operatorsσ x ,σ y ,σ z , thus generating white noise on the state. 32,33 In the inset of Fig. 1a, we show typical experimental curves for the work W ρ (θ, θ) calculated according to Eq.…”
Section: Resultsmentioning
confidence: 99%